Demure Heroines Expressing Sexual Desire. Hints of traditional motifs in popular Hindi cinema - Ciolfi, Sabrina (Acta Orientalia Vilnensia, 2011)
Università degli Studi di Milano In some of the most successful and representative popular Hindi films released between the 1990s and the early 2000s, the depiction of amorous feelings often takes traditional forms. The reference here is essentially to those films that come more or less within the broad category of classical family dramas: love stories that come up against all sorts of opposition, characterised by the celebration of the traditional Hindu values and the sacrality of the Indian joint-family institution. A particularly interesting aspect emerging here lies in the way in which the sexual desire of the heroine—typically a chaste and virtuous maiden—finds representation. On the strength of studied re-elaboration of traditional themes and motifs, these films achieve high levels of stylistic inventiveness and poetic refinement, albeit often limited to certain individual sequences. The apparent purpose of this aesthetic sophistication is to endow amorous feelings—always leading inexorably in the direction of marriage—with an aura of purity and authenticity. Indeed, it is a matter of sentiments so noble and intense as to win over the consent and blessing of the families by the end of the film. The paper proposes to identify and analyse the conscious use of these traditional motifs in some of the most representative films in this area.